KONSUMSI MAKANAN CEPAT SAJI (FAST FOOD) DAN KELUHAN DISMENORE PRIMER PADA REMAJA SANTRIWATI DI PONDOK PESANTREN X KABUPATEN BANYUMAS - Rudatiningtyas, Ulfa Fadilla; Anasari, Tri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Primary dysmenorrhea is menstrual pain characterized by discomfort in the lower abdominal area. One of the factors that may trigger this condition is the consumption of fast food. Fast food is known as a type of practical meal that is prepared and served quickly. However, excessive consumption of such food can increase the level of prostaglandin hormones in the body, which in turn causes menstrual pain. This study aims to determine the relationship between fast food consumption habits and the incidence of primary dysmenorrhea among female students at Pondok Pesantren X. The research instrument used was a questionnaire to obtain primary data. The collected data were analyzed univariately using frequency distribution and bivariately using the Chi-Square test. The results showed that 94.0% of the students experienced primary dysmenorrhea, and 87.2% of them were categorized as frequent fast food consumers. Based on the bivariate test results, a p-value of 0.000 was obtained, indicating a significant relationship between fast food consumption habits and the incidence of primary dysmenorrhea among the students.Keywords: Primary Dysmenorrhea, Fast Food Consumption